High velocity impact induced microstructure evolution during deposition of cold spray coatings: A review - Luo, Xiao-Tao; Li, Cheng-Xin; Shang, Fu-Lin; Yang, Guan-Jun; Wang, Yu-Yue; Li, Chang-Jiu (Surface & coatings technology, 2014)
Cold spray is a fast growing coating process involving in high strain rate deformation of spray particles. Early investigations stressed the retaining of feedstock microstructures into deposits. However, in recent years, metastable microstructures including high density of dislocations, nanosized grains and localized amorphous phase have been frequently observed through detailed microstructure characterization and it was found that those metastable microstructures remarkably affect the coating properties. In this review article, the evolution mechanisms of metastable microstructure in a cold spray coating during deposition of spray particles were examined in terms of in-situ densification, residual stress, dislocation multiplication, grain refining, phase transformation and amorphization through typical materials. Feedstock microstructure design, in-process control and material selection are essential approaches to acquire the coatings with desired microstructure. •High speed impact induced microstructure evolution during deposition was reviewed.•Residual stress in cold sprayed coatings can be either tensile or compressive.•Tamping effect can be used to prepare super-hard coating by porous powder design.•Metastable microstructures benefit improving coating properties.